Creative Approach in Teaching the Chapter of Metals Working (Eurasian Journal of Learning and Academic Teaching, 2022)
This article talks about the special features of the science of technology, attracting students to the world of spiritual and material culture on the basis of science, the types of students and the development of their individual characteristics.